Age and female gender associated with periodontal disease in Japanese patients with rheumatoid arthritis: Results from self-reported questionnaires from the IORRA cohort study. Issue 3 (3rd May 2020) - Furuya, Takefumi; Inoue, Eisuke; Tanaka, Eiichi; Maeda, Shigeru; Ikari, Katsnori; Taniguchi, Atsuo; Yamanaka, Hisashi
Abstract: Objectives: This study aimed to evaluate the prevalence of, and the factors associated with, periodontal disease in Japanese patients with rheumatoid arthritis (RA). Methods: Patients with RA enrolled in the Institute of Rheumatology Rheumatoid Arthritis (IORRA) cohort completed three self-administered questionnaires including questions about recent gingival bleeding during toothbrushing, a recent diagnosis of periodontitis by a dentist, and any history of periodontitis. Logistic regression analyses were used to evaluate associations with clinical variables for each questionnaire. Results: Among 5600 Japanese patients with RA, 31.0%, 18.3%, and 20.4% of patients self-reported recent gingival bleeding during toothbrushing, a recent diagnosis of periodontitis by a dentist, and a history of periodontitis, respectively. In multivariate models, younger age, fracture history, Japanese Health Assessment Questionnaire-Disability Index (JHAQ-DI), and prednisolone dosage were significantly ( p  < .05) associated with recent gingival bleeding during toothbrushing. Older age, female gender, and ever-smoker status were significantly correlated with a recent diagnosis of periodontitis. Conclusion: Many Japanese patients with RA experience gingival bleeding during toothbrushing and are diagnosed with periodontitis. Age, female gender, ever-smoker status, fracture history, JHAQ-DI, and prednisolone dosage appeared to be associated with periodontal disease in Japanese patients with RA.